François Bon et la «diction du monde» - Roche, Anne (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
François Bon's novels seem to deal with marginal characters and subjects: unemployment, wreckage of industry, drugs, petty crimes, prison... His work is actually a lyrical eulogy to a disappearing modernity, but reveals a sophisticated formal research: it shapes itself on the I mould of Greek tragedy, while kneading more current forms of language.
François Bon, "phrasing the world"